Extreme Positive Ionosphere Storm Triggered by a Minor Magnetic Storm in Deep Solar Minimum Revealed by FORMOSAT‐7/COSMIC‐2 and GNSS Observations. Issue 2 (5th February 2021) - Rajesh, P. K.; Lin, C. H.; Lin, C. Y.; Chen, C. H.; Liu, J. Y.; Matsuo, T.; Chen, S. P.; Yeh, W. H.; Huang, C. Y.
Abstract: This study examines an unexpected and extreme positive ionospheric response to a minor magnetic storm on August 5, 2019 by using global ionosphere specification (GIS) 3D electron density profiles obtained by assimilating radio occultation total electron content (TEC) measurements of the recently launched FORMOSAT‐7/COSMIC‐2 satellites, and ground‐based global navigation satellite system (GNSS) TEC. The results reveal ∼300% enhancement of equatorial ionization anomaly (EIA) crests, appearing over 200–300 km altitudes, and a much intense localized density enhancement over the European sector. These are the most intense ionospheric response that has ever been detected for a small magnetic storm with Dst ∼ −53 nT (SYM‐H ∼ −64 nT). The enhancements are validated by using global ionosphere map (GIM) TEC and ground‐based GNSS TEC. The GIS vertical electron density structures during the storm are examined to understand the physical processes giving rise to such an intense ionosphere response during deep solar minimum conditions when the background electron density is very low. Altitude variations and poleward shifts of the locations of the EIA crests indicate that prompt penetration electric fields (PPEF) play an important role in producing the observed positive storm responses, with the storm‐induced equatorward circulation supporting the plasma accumulation against recombination losses. Additional physical mechanisms are required to fully explain the unexpected electron density enhancements for this minor storm event. Plain Language Summary: Ionospheric measurements by the new FORMOSAT‐7/COSMIC‐2 mission detected extreme and unexpected electron density enhancements during a weak magnetic storm on August 5, 2019. The electron density increased by >300% over Asia and Africa compared to previous day's values, and over Europe the increase was about 800%. Scientists previously showed large electron density increase when major magnetic storms occur, but such intense enhancements by a weak magnetic storm is not reported before. This may be due to the lack of continuous global electron density measurements previously. Using FORMOSAT‐7/COSMIC‐2 satellite GPS data, we have developed 3D global ionospheric electron densities for every hour on each day, and for the first‐time measurements are now available to study such variations. The new observations show that when solar activity is very low, a weak magnetic storm could produce very large variations, disrupting the ionosphere similar to that during severe magnetic storms. This study demonstrates the potential of FORMOSAT‐7/COSMIC‐2 measurements to capture such electron density variations. Detailed analysis shows that the magnetic storm modified electric field and wind, which contributed to the density enhancements. The results also suggest additional physical processes during magnetic storms in low solar activity periods than previously considered. Key Points: Global 3D ionosphere built from FORMOSAT‐7/COSMIC‐2 and GNSS data shows extreme positive effects during a minor magnetic storm (Dst ∼ −53 nT) Dayside low‐latitude/midlatitude ionosphere shows storm‐time enhancement in total electron content by ∼200% and in density at 200–300 km by ∼300% Along with penetration electric field and storm‐time wind, rapid thermosphere expansion and low‐latitude downwelling could also be important